KEPEMIMPINAN DALAM PENINGKATKAN MUTU PENDIDIKAN MELALUI MANAJEMEN BERBASIS SEKOLAH DI MI ADDINIYAH JIYU MOJOKERTO - Jefri Angga Yuda, Mukhamad (ILJ: Islamic Learning Journal, 2024)
Leadership ranks at the top, namely an indicator of the progress of a school/ madrasah institution. The leadership of the school/madrasah principal is a very basic element in terms of the authority to make policies to improve the quality of education whose results can be used as an indicator of the progress of a school/madrasah. The leader is the spirit, the driving force for the progress of the madrasa in terms of empowering all existing resources, namely human resources and other resources to achieve their goals. Creativity arises as a result of empowering individuals. In the school context, the Principal must empower his staff, both educators and educational staff and their students, because empowerment will generate self-confidence in those who are empowered. This self-confidence will foster unexpected creativity. The problem that occurs is the lack of role of the school principal in improving the quality of education at MI Addiniyah Jiyu Kec. Kutorejo Kab. Mojokerto which until now has not been resolved in line with the complexity of environmental changes, both in terms of planning, organizing, implementing and supervising. The emergence of this problem is due to the not yet optimal empowerment of the Principal's raw input; empowerment of instrumental inputs which include curriculum, infrastructure, costs and human resources, plus the not optimal involvement of environmental inputs consisting of the community and stakeholders.